ANALYSIS OF RANDOM EARLY DETECTION AND HIERARCHICAL TOKEN BUCKET METHOD ON LOCAL AREA NETWORK WIRELESS - Shaidul Maula; Anwar; Jamilah; Mark G. Maffett (Bulletin of Engineering Science, Technology and Industry, 2023)
One of the problems that internet users often face is slow internet access. This problem can occur because there is no bandwidth management system in use. The Random Early Detection and Hierarchical Token Bucket methods are good methods. However, it is not yet known which is the best between the two. Research needs to be carried out to determine the comparison of network quality using these two methods. This research aims to determine the quality of networks that apply the Random Early Detection and Hierarchical Token Bucket methods whether they are given noise injection or not. This research data was collected by testing the wireless local area network. The collected data is analyzed using QoS. The results show that the implementation of the Hierarchical Token Bucket method is of better quality, it can be seen with a throughtput value of 879128 bps, a delay value of 8 ms, a jitter value of 11,041 ms and a packet loss value of 0%. On the other hand, the Hierarchical Token Bucket method was given Noise Injection with a throughput of 582716 bps, a delay value of 15,427 ms, a jitter value of 21,924 ms and a packet loss value of 2.8%. Meanwhile, the application of the Random Early Detection method obtains quality with a throughput value of 816,287 bps, a delay value of 8,673 ms, a jitter value of 12,591 ms and a packet loss value of 0%. On the other hand, the Random Early Detection method is given Noise Injection with a throughput value of 704778 bps, a delay value of 11,154 ms, a jitter value of 15,565 ms and a packet loss value of 2.14%.